2022
DOI: 10.18775/ijmsba.1849-5664-5419.2014.85.1002
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Related Stressors and Performance: The Case of Lebanese Employees During the Pandemic

Abstract: In the aftermath of Covid-19 and the national lockdown, various firms and companies were obliged to operate remotely from work. This provided several challenges and opportunities to both employees and employers. The reason for carrying this study goes to this new stressful and challenging subject that took over the globe. In this study, the results for the effect of job stress related to the Covid-19 pandemic and employees’ performance in Lebanon will be discussed. The effect of the three main independent stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, to alleviate stress during confinement or similar circumstances, governments should contemplate public policies about regulations on paid work, flexible or remote working hours, and clear guidelines to promote employees' emotional and mental well-being [59,60]. Paid parental or family leave remains a crucial support for families in managing care responsibilities for children or other dependents [61]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to alleviate stress during confinement or similar circumstances, governments should contemplate public policies about regulations on paid work, flexible or remote working hours, and clear guidelines to promote employees' emotional and mental well-being [59,60]. Paid parental or family leave remains a crucial support for families in managing care responsibilities for children or other dependents [61]).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the global crises induced by the COVID-19 pandemic could compromise the commitments of the world to the 2030 Agenda for Sustainable Development [17]. Several academic studies have focused on sustainability during the COVID-19 pandemic (i.e., [18][19][20]). Under these circumstances, budgeting would play a paramount role [21].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of economic crisis, two elements would be as essential reason of stress that employees have to deal with: Job insecurity and financial loss. Job insecurity is associated with distress and negative emotions that can be stressful for employees as experience to pass through which is the concern about the continuity of the job in the future (Rabih El Kabbout, 2022). Due to the Covid-19 outbreak, followed by the economic crisis short working hours and stay lay-off and redundancies happened; which will estimate to affect the performance of employees.…”
Section: Work Life Balance and Employee Performancementioning
confidence: 99%
“…Due to the Covid-19 outbreak, followed by the economic crisis short working hours and stay lay-off and redundancies happened; which will estimate to affect the performance of employees. However, the study conducted by (Rabih El Kabbout, 2022) found that job insecurity and financial loss will not affect the performance of employees instead this will lead them to prove that their performance is high due to the fear of losing their jobs, beside they are already facing economic crisis they will be able to normalize the stress of financial loss. Job security is the priority for the employees; they will maintain a high performance and not let any struggle face such as work life balance so this will help us formulate: Hypothesis 3: During economic crisis, work life balance has a positive effect on employee's performance.…”
Section: Work Life Balance and Employee Performancementioning
confidence: 99%